Experimental and computational studies of melting of the spinel phase in the Fe–Al–O ternary system. (September 2020) - Agca, Can; Lindwall, Greta; McMurray, Jake W.; Neuefeind, Jörg C.; Liu, Zi-Kui; Navrotsky, Alexandra
Abstract: The melting behavior of spinel in the Fe–Al–O system at high temperatures (1500–1800 °C) was studied by a combination of experimental and computational investigations. Differential thermal analysis (DTA) at ultra-high temperatures coupled with cooling traces on CO2 laser-heated levitated samples provided melting temperatures and the heats of fusion of (Fe, Al)3 O4 spinel phases. The experimental results are in fair agreement with the predictions using a published CALPHAD description and areas for modeling improvement are identified. New insights into the melting of defect spinel are provided.